Get (Com)Passionate for Wellbeing: Designing a Virtual Reality Wellbeing Intervention for Emerging Adults with Chronic Medical Conditions - Quesnel, Denise; Riecke, Bernhard E (Mind & Life 2023 Summer Research Institute (SRI), 2023)
Motivation: Emerging adults with chronic health conditions (EA-CHCs) are at risk of deteriorating quality of life outcomes and are a vulnerable group facing unsurmountable adversity and obstacles to mental health supports. While technology has explored in many scenarios as a solution for disease management, struggles remain with sustainable implementation and ‘optimization’ of therapeutic outcomes for this population. Proposed Solution: We will use our Virtual Reality Intervention (VRI) research and design framework to build upon "Awedessey" (our publicly exhibited and tested VRI for transformative emotions and social connection) into a VRI for, and with EA-CHC end user co-designers. While there is no panacea intervention, we will merge transformative VRI design, compassion training, and peer support – principles with extensive therapeutic evidence – into a single intervention. To deepen therapeutic outcomes, the VRI can be implemented within, and adjacent to conventional psychoeducational programs and services, and in end-users homes. Prior Work: "Awedessey" was initially designed by iSpace Lab at Simon Fraser University and Charité — Universitätsmedizin Berlin for an 8-month long study on mitigation of psychological stressors astronauts may experience on long-duration exploratory space missions. Goals were: • Countering feelings of isolation • Evoking connection to self, humanity, nature, and Earth • Facilitating awe and wonder • Prompting introspection, meditation, and relaxation • In keeping a Loving-Kindness Meditation within a transformative experience design framework, Awedessey expanded to the general public in Vancouver, Berlin, and Moscow with minimal design changes. Positive feedback and insights emphasized potential benefits for young people with chronic mental and physical health conditions. However, optimal therapeutic outcomes through Awedessey will require collaborative VRI design and decision-making with EA-CHCs, because when they aren’t involved in the design process, digital interventions often result in ineffectiveness, lack of fit, and disengagement for young people. Key Opportunities and Next Steps: VRIs and compassionate abilities show therapeutic potential for young people with chronic health conditions. We will create and evaluate the VRI through robust participatory and rapid design methodology to avoid technological obsolescence, and: 1. Sustain project feasibility by building upon our VRI framework and template (Awedessey); 2. Ensure impact and relevance to EA-CHCs, with strategic implementation achieved through codesign methods (hands-on testing, co-design sessions, interviews, and contextual evaluations); six EA-CHCs aged 16-25 (end users) and four stakeholders (healthcare professionals and therapists) will be recruited via BC Children’s Hospital (BCCH) Centre for Mindfulness, disease-specific paediatric & adult clinics in Lower Mainland of Vancouver, BC.
Keywords: Riecke; Riecke_2023; bernhard-riecke; denise-quesnel; poster; posterWithoutPaper; proj--awedyssey